Perpendicular Local Magnetization Under Voltage Control in Ni Films on Ferroelectric BaTiO3 Substrates - Ghidini, Massimo; Maccherozzi, Francesco; Moya, Xavier; Phillips, Lee C.; Yan, Wenjing; Soussi, Jordane; Métallier, Nicolas; Vickers, Mary E.; Steinke, Nina -J.; Mansell, Rhodri; Barnes, Crispin H. W.; Dhesi, Sarnjeet S.; et al. (Advanced materials (Weinheim), 2015)
High‐resolution magnetoelectric imaging is used to demonstrate electrical control of the perpendicular local magnetization associated with 125 nm‐wide magnetic stripe domains in 100‐nm‐thick Ni films. This magnetoelectric coupling is achieved in zero magnetic field using strain from ferroelectric BaTiO3 substrates to control perpendicular anisotropy imposed by the growth stress. These findings may be exploited for perpendicular recording in nanopatterned hybrid media.